Role of RNA N6-Methyladenosine Modification in Male Infertility and Genital System Tumors - Liu, Shuai; Lao, Yongfeng; Wang, Yanan; Li, Rongxin; Fang, Xuefeng; Wang, Yunchang; Gao, Xiaolong; Dong, Zhilong (Frontiers in Cell and Developmental Biology, 2021)
Epigenetic alterations, particularly RNA methylation, play a crucial role in many types of disease development and progression. Among them, N6-methyladenosine (m6A) is the most common epigenetic RNA modification, and its important roles are not only related to the occurrence, progression, and aggressiveness of tumors but also affect the progression of many non-tumor diseases. The biological effects of RNA m6A modification are dynamically and reversibly regulated by methyltransferases (writers), demethylases (erasers), and m6A binding proteins (readers). This review summarized the current finding of the RNA m6A modification regulators in male infertility and genital system tumors and discussed the role and potential clinical application of the RNA m6A modification in spermatogenesis and male genital system tumors.